UTILIZATION OF MANGROVE FRUIT (Sonneratia caseolaris ) AS A PRESERVATIVE TILAPIA (Oreochromis niloticus) - Laila Umaya; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTTilapia is a food ingredient that is easily subject to decay and damage (perishable food). This damage can occur biochemically as well as microbiologically. Mangrove fruit (Sonneratia caseolaris) contains antibacterial compounds that can inhibit the growth of microorganisms that cause decay in fishery products. Therefore, this study was conducted to determine the effect of the concentration of mangrove fruit extract on the preservation of tilapia (Oreochromis niloticus). The soaking treatment of mangrove fruit extract used concentrations of 0%, 2%, 3% and 4%. This study used a non-factorial complete randomized design (CRD). The tested parameters were organoleptic including appearance values (eyes, gills, mucus), odor values, incision values, and texture values. The results showed that the most effective treatment for preservation using mangrove fruit extract in tilapia was soaking with a concentration of 4%, having an organoleptic value of eye appearance of 7.67 (convex eyeballs, cornea and clear pupils), gill appearance 7.44 (dark red gills), body surface mucus 7.53 (clear, transparent mucus layer), tilapia smell 7.36 (fresh smell, type specificity), tilapia meat 7.53 (brilliant meat incision), texture value 7.84 (dense, compact and elastic texture). The best treatment can inhibit bacterial growth and maintain the quality of tilapia. Keywords: Mangrove, Organoleptic, Tilapia